Perennial Grasses on Stony Sandy Loam Arenosol: Summary of Results of Long-Term Experiment in Northern Europe Region (1995–2024) - Liudmila Tripolskaja; Asta Kazlauskaite-Jadzevice; Almantas Razukas; Eugenija Baksiene (Plants)
Grasses can sustain soil functions despite nutrient depletion, which can have serious consequences for soil processes and ecosystem services. This paper summarizes the results of the long-term experiment (1995–2024) carried out in Arenosol within a temperate climate zone, focusing on the productivity of natural and managed grasslands; their succession changes over time, and so do the effects on soil chemical properties, and soil organic carbon (SOC) sequestration. The results indicated that two land uses—abandoned land (AL) and grassland fertilized with mineral fertilizers (MGf)—can be effectively applied to prevent Arenosol soil degradation. SOC accumulation occurs more rapidly in AL soils, and their chemical properties show less change over time. The ability of grasses to sequester SOC is better reflected by SOC stocks across the Ah horizon, where thickness varies over long-term grassland use. Significant changes in soil properties were observed more than 20 years after converting arable to herbaceous land use. While MGf has the highest biomass productivity, the use of fertilizers leads to soil acidification. The biomass productivity of AL and MGf increased with longer grassland use; however, in MG, productivity decreased without fertilizers, reaching AL’s productivity levels after 20 years. As the age of AL increased, plant biodiversity decreased, and drought-resistant plants began to spread.